A kind of C80 recycled fine aggregate concrete and preparation method thereof

By pretreating basalt fibers and potassium hydroxide solutions in C80 regenerated fine aggregate concrete, the problem of degradation of regenerated fine aggregate concrete is solved, and concrete products with high strength and good durability are achieved.

CN117125935BActive Publication Date: 2025-04-08CHANGZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311064864.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-04-08
Estimated Expiration
2043-08-23

AI Technical Summary

Technical Problem

When regenerated fine aggregates completely replace natural sand in concrete, they will cause the concrete to lose its easiness, density, permeability, mechanical strength and elastic modulus, and their durability performance will be poor.

Method used

The C80 regenerated fine aggregate concrete formula is used, including regenerated fine aggregate, basalt fibers, natural coarse aggregates and gelling materials, and pretreatment is improved by impregnating regenerated fine aggregates and basalt fibers in potassium hydroxide solution to improve the physical properties of the aggregate and the secondary hydration effect of the gelling materials.

Benefits of technology

It improves the mechanical properties and durability of regenerated fine aggregate concrete, so that it has high compactness and strength after forming, and significantly improves compressive strength and chlorine salt corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005275354960000131
    Figure GDA0005275354960000131
  • Figure GDA0005275354960000132
    Figure GDA0005275354960000132
  • Figure GDA0005275354960000141
    Figure GDA0005275354960000141
Patent Text Reader

Abstract

The present invention belongs to the technical field of building materials, and specifically relates to a C80 recycled fine aggregate concrete and a preparation method thereof, comprising the following raw materials by mass fraction: 1205-1260 parts of natural coarse aggregate, 425-455 parts of recycled fine aggregate, 2.64-7.93 parts of basalt fiber, 540-580 parts of cementitious material, 5.4-5.8 parts of water reducer, and 111-124 parts of water. The present invention first pre-treats the recycled fine aggregate and basalt fiber mixture with potassium hydroxide solution to improve the performance of the recycled fine aggregate and basalt fiber, and then mixes the pre-treated mixture with other raw materials to prepare concrete with high mechanical strength and good resistance to chloride ion penetration, which is beneficial to the application of recycled fine aggregate from construction waste in concrete and its products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a C80 recycled fine aggregate concrete and a preparation method thereof. Background Art

[0002] Recycled fine aggregate is a particle with a particle size of less than 4.75 mm obtained by crushing and screening concrete, mortar, stone or bricks and tiles in construction waste. Compared with natural sand, recycled fine aggregate has old mortar adhering to the surface of the aggregate or mixed in it, which makes the recycled fine aggregate have the characteristics of lower apparent density and bulk density, higher crushing value and water absorption rate, more microcracks, and poor interface performance. If recycled fine aggregate completely replaces natural sand in concrete, it will lead to a decrease in concrete workability, density, permeability, mechanical strength and elastic modulus, as well as an increase in drying shrinkage and creep deformation. Xiao Jianzhuang et al. pointed out in "Principles of Waste Concrete Recycling and Basic Issues of Recycled Concrete" that compared with ordinary concrete, the 28d compressive strength of concrete with appropriate proportion of recycled fine aggregate is reduced by about 15%, and the 180d compressive strength is reduced by about 12% compared with ordinary concrete. Therefore, the performance and quality of recycled fine aggregate are inferior to natural sand, and its utilization rate in structural concrete is low. Summary of the invention

[0003] In order to overcome the deficiencies in the prior art, the present invention provides a C80 recycled fine aggregate concrete, which has excellent mechanical properties and durability, and is conducive to the application of recycled fine aggregate from construction waste in concrete and its products.

[0004] The technical solution provided by the present invention is: a C80 recycled fine aggregate concrete, comprising the following components in parts by weight: 425-455 parts of recycled fine aggregate, 2.64-7.93 parts of basalt fiber (accounting for 0.1%-0.3% of the volume fraction of concrete), 1205-1260 parts of natural coarse aggregate (the mass ratio of coarse aggregate to fine aggregate is 2.8), 540-580 parts of cementitious material (the bone-cement ratio is 3), wherein the cementitious material comprises: cement, fly ash, silica fume, mineral powder, and the mass ratio thereof is 14:3:2:1; 5.4-5.8 parts of water reducer (accounting for 1% of the mass of the cementitious material); and 111-124 parts of water (the water-cement ratio is 0.21).

[0005] Preferably, the natural coarse aggregate is crushed stone of Class III or above as specified in GB / T14685-2022, with a diameter of 4.75-31.50 mm.

[0006] Preferably, the recycled fine aggregate is Class III or above recycled fine aggregate specified in GB / T25176-2010, and has a particle size of 0.15-4.75 mm.

[0007] Preferably, the basalt fiber has a fiber length of 6 mm, a single fiber diameter of 7-15 μm, and a density of 2.63-2.65 g / cm 3 , elastic modulus 91-110GPa, tensile strength 3000-4800MPa, chemical stability in 2M HCl is 2.2, and chemical stability in 2MNaOH is 2.75.

[0008] Preferably, the cement is ordinary Portland cement with a strength grade of P.O52.5.

[0009] Preferably, the fly ash is Class I fly ash.

[0010] Preferably, the mass content of SiO2 in the silicon powder is ≥94%.

[0011] Preferably, the mineral powder is S105 grade blast furnace mineral powder.

[0012] Preferably, the water reducing agent is a polycarboxylic acid high-efficiency water reducing agent with a water reducing efficiency of 40%.

[0013] A method for preparing C80 recycled fine aggregate concrete comprises the following steps:

[0014] S1: Weigh each component according to mass fraction;

[0015] S2: Immerse the recycled fine aggregate and basalt fiber in a 10-20wt% potassium hydroxide solution, the mass ratio of the recycled fine aggregate to the potassium hydroxide solution is (425-455):1000, stir evenly, let stand for 24-48 hours, and stir evenly every 6-8 hours;

[0016] S3: The recycled fine aggregate and basalt fiber mixture is sieved out with a sieve, and after the mixture is rinsed with clean water, it is placed in a high-temperature oven at 105°C for drying until the aggregate state is saturated and surface dry, and then stored for later use; during the drying period, the mixture is turned over and stirred every 10 minutes;

[0017] S4: Add the mixture, natural coarse aggregate and 40% water into the mixer and mix at a speed of 80-100 r / min for 60 s;

[0018] S5: Add the gel material into the mixer and stir at a speed of 80-100 r / min. During the stirring process, slowly add the water reducing agent and 60% of water into the mixer and stir evenly to obtain concrete.

[0019] Furthermore, the concentration of the potassium hydroxide solution is 15 wt %.

[0020] Furthermore, the standing time is 24 hours.

[0021] Compared with the prior art, the beneficial effects achieved by the reverse invention are:

[0022] S1: The proportion of each component in the present invention is reasonable, the prepared C80 recycled fine aggregate concrete has good workability, high density after molding, and the strength can reach the expected level.

[0023] S2: The present invention uses potassium hydroxide solution of appropriate concentration to pretreat the mixture of recycled fine aggregate and basalt fiber, which is an effective method to improve the workability and strength of recycled fine aggregate concrete. On the one hand, potassium hydroxide reacts weakly with silicon in the pores of recycled fine aggregate to generate needle-shaped K-Si-Hgel, which fills the internal pores of the aggregate and improves the physical properties of the recycled fine aggregate. When the aggregate reaches a saturated surface dry state, the moisture absorbed by the aggregate will have an internal curing effect, which will promote the secondary hydration of the cementitious material after the concrete is made, generate dense hydration products, and improve the mechanical properties and durability of the concrete. On the other hand, the Na in the basalt fiber + K in potassium hydroxide solution + Produces ion exchange, K + The generated surface compressive stress will compensate the external force in some way, thereby limiting stress concentration. A shell with a plate-like structure is formed on the fiber surface, which increases the strength and thus improves the comprehensive performance of concrete. There is a good synergistic effect between recycled fine aggregate and basalt fiber, which improves the mechanical properties and durability of recycled fine aggregate concrete.

[0024] S3: Using recycled fine aggregate to completely replace natural sand not only alleviates the problem of increasing shortage of natural sand, but also the invention is simple to prepare, convenient to construct, and has a wide range of applications. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in combination with the embodiments of the specification. The following implementation methods are only used to more clearly illustrate the technical solutions of the present invention, and cannot be used to limit the protection scope of the present invention.

[0026] The present invention tests the physical properties of recycled fine aggregate according to GB / T14684-2022 "Sand for Construction", tests the moisture state of aggregate according to GB / T14684, determines the classification of recycled fine aggregate according to GB / T25176-2010 "Recycled Fine Aggregate for Concrete and Mortar", tests the slump of recycled fine aggregate concrete according to GB / T50080-2016 "Standard for Test Methods for Performance of Ordinary Concrete Mixtures", and tests the 28d compressive strength of recycled fine aggregate concrete according to GB / T50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete".

[0027] In the following examples and comparative examples, the raw materials used are: P.O52.5 ordinary Portland cement, Class III natural coarse aggregate specified in GB / T14685-2022, Class III recycled fine aggregate specified in GB / T25176-2010, silica fume with SiO2 mass content ≥94%, Class I fly ash, S105 blast furnace ore powder, length 6 mm, diameter 7-15 μm, density 2.63-2.65 g / cm 3 , basalt fiber with elastic modulus of 91-110GPa, tensile strength of 3000-4800MPa, chemical stability of 2.2 in 2M HCl, and chemical stability of 2.75 in 2MNaOH.

[0028] Example 1

[0029] S1: Weigh the following raw materials in parts by weight: 445 parts of Class III recycled fine aggregate (the aggregate water absorption rate is measured to be 10%), 5.28 parts of basalt fiber, 1245 parts of natural coarse aggregate, 392 parts of cement, 84 parts of fly ash, 56 parts of silica fume, 28 parts of mineral powder, 5.6 parts of water reducer, and 120 parts of water;

[0030] S2: Add recycled fine aggregate, basalt fiber and 15wt% potassium hydroxide solution into a mixer, stir evenly at a speed of 90r / min, let stand for 24h, and stir evenly every 6h; wherein the mass ratio of recycled fine aggregate to potassium hydroxide solution is 445:1000;

[0031] S3: Sieve the recycled fine aggregate and basalt fiber mixture with a sieve, rinse the mixture with clean water for 3 times, and then dry it in a high-temperature oven at 105°C until the aggregate is saturated and dry, and then store it for later use; stir it every 10 minutes during the drying period;

[0032] S4: Add the mixture, natural coarse aggregate and 40% of water into the mixer and mix at a speed of 90 r / min for 60 s;

[0033] S5: adding cement, fly ash, silica powder and mineral powder into a mixer, stirring at a speed of 90 r / min, slowly adding a water reducer and 60% of water into the mixer during the stirring process, stirring evenly, and obtaining a concrete mixture;

[0034] S6: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0035] Example 2

[0036] S1: Weigh the following raw materials in parts by weight: 425 parts of Class III recycled fine aggregate (the aggregate water absorption rate is measured to be 10%), 5.28 parts of basalt fiber, 1205 parts of natural coarse aggregate, 378 parts of cement, 81 parts of fly ash, 54 parts of silica fume, 27 parts of mineral powder, 5.4 parts of water reducer, and 111 parts of water;

[0037] S2: Add recycled fine aggregate, basalt fiber and 15wt% potassium hydroxide solution into a mixer, stir evenly at a speed of 90r / min, let stand for 24h, and stir evenly every 6h; wherein the mass ratio of recycled fine aggregate to potassium hydroxide solution is 425:1000;

[0038] S3: Sieve the recycled fine aggregate and basalt fiber mixture with a sieve, rinse the mixture with clean water for 3 times, and then dry it in a high-temperature oven at 105°C until the aggregate is saturated and dry, and then store it for later use; stir it every 10 minutes during the drying period;

[0039] S4: Add the mixture, natural coarse aggregate and 40% of water into the mixer and mix at a speed of 90 r / min for 60 s;

[0040] S5: adding cement, fly ash, silica powder and mineral powder into a mixer and stirring at a speed of 90 r / min. During the stirring process, slowly adding a water reducing agent and 60% of water into the mixer and stirring evenly to obtain a concrete mixture;

[0041] S6: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0042] Example 3

[0043] S1: Weigh the following raw materials in parts by weight: 455 parts of Class III recycled fine aggregate (the aggregate water absorption rate is measured to be 10%), 5.28 parts of basalt fiber, 1260 parts of natural coarse aggregate, 406 parts of cement, 87 parts of fly ash, 58 parts of silica fume, 29 parts of mineral powder, 5.8 parts of water reducer, and 124 parts of water;

[0044] S2: Add recycled fine aggregate, basalt fiber and 15wt% potassium hydroxide solution into a mixer, stir evenly at a speed of 90r / min, let stand for 24h, and stir evenly every 6h; wherein the mass ratio of recycled fine aggregate to potassium hydroxide solution is 455:1000;

[0045] S3: Sieve the recycled fine aggregate and basalt fiber mixture with a sieve, rinse the mixture with clean water for 3 times, and then dry it in a high-temperature oven at 105°C until the aggregate is saturated and dry, and then store it for later use; stir it every 10 minutes during the drying period;

[0046] S4: Add the mixture, natural coarse aggregate and 40% of water into the mixer and mix at a speed of 90 r / min for 60 s;

[0047] S5: adding cement, fly ash, silica powder and mineral powder into a mixer, stirring at a speed of 90 r / min, slowly adding a water reducer and 60% of water into the mixer during the stirring process, stirring evenly, and obtaining a concrete mixture;

[0048] S6: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0049] Example 4

[0050] S1: Weigh the following raw materials in parts by weight: 445 parts of Class III recycled fine aggregate (the aggregate water absorption rate is measured to be 10%), 2.64 parts of basalt fiber, 1245 parts of natural coarse aggregate, 392 parts of cement, 84 parts of fly ash, 56 parts of silica fume, 28 parts of mineral powder, 5.6 parts of water reducer, and 120 parts of water;

[0051] S2: Add recycled fine aggregate, basalt fiber and 15wt% potassium hydroxide solution into a mixer, stir evenly at a speed of 90r / min, let stand for 24h, and stir evenly every 6h; wherein the mass ratio of recycled fine aggregate to potassium hydroxide solution is 445:1000;

[0052] S3: Sieve the recycled fine aggregate and basalt fiber mixture with a sieve, rinse the mixture with clean water for 3 times, and then dry it in a high-temperature oven at 105°C until the aggregate is saturated and dry, and then store it for later use; stir it every 10 minutes during the drying period;

[0053] S4: Add the mixture, natural coarse aggregate and 40% of water into the mixer and mix at a speed of 90 r / min for 60 s;

[0054] S5: adding cement, fly ash, silica powder and mineral powder into a mixer, stirring at a speed of 90 r / min, slowly adding a water reducer and 60% of water into the mixer during the stirring process, stirring evenly, and obtaining a concrete mixture;

[0055] S6: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0056] Example 5

[0057] S1: Weigh the following raw materials in parts by weight: 445 parts of Class III recycled fine aggregate (the aggregate water absorption rate is measured to be 10%), 7.93 parts of basalt fiber, 1245 parts of natural coarse aggregate, 392 parts of cement, 84 parts of fly ash, 56 parts of silica fume, 28 parts of mineral powder, 5.6 parts of water reducer, and 120 parts of water;

[0058] S2: Add recycled fine aggregate, basalt fiber and 15wt% potassium hydroxide solution into a mixer, stir evenly at a speed of 90r / min, let stand for 24h, and stir evenly every 6h; wherein the mass ratio of recycled fine aggregate to potassium hydroxide solution is 445:1000;

[0059] S3: Sieve the mixture with a sieve, rinse the mixture with clean water for 3 times, and then dry it in a high-temperature oven at 105°C until the aggregate is saturated and dry, and then store it for later use; stir it every 10 minutes during the drying period;

[0060] S4: Add the mixture, natural coarse aggregate and 40% of water into the mixer and mix at a speed of 90 r / min for 60 s;

[0061] S5: adding cement, fly ash, silica powder and mineral powder into a mixer, stirring at a speed of 90 r / min, slowly adding a water reducer and 60% of water into the mixer during the stirring process, stirring evenly, and obtaining a concrete mixture;

[0062] S6: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0063] Example 6

[0064] S1: Weigh the following raw materials in parts by weight: 445 parts of Class III recycled fine aggregate (the aggregate water absorption rate is measured to be 10%), 5.28 parts of basalt fiber, 1245 parts of natural coarse aggregate, 392 parts of cement, 84 parts of fly ash, 56 parts of silica fume, 28 parts of mineral powder, 5.6 parts of water reducer, and 120 parts of water;

[0065] S2: Add recycled fine aggregate, basalt fiber and 20wt% potassium hydroxide solution into a mixer, stir evenly at a speed of 90r / min, let stand for 24h, and stir evenly every 6h; wherein the mass ratio of recycled fine aggregate to potassium hydroxide solution is 445:1000;

[0066] S3: Sieve the recycled fine aggregate and basalt fiber mixture with a sieve, rinse the mixture with clean water for 3 times, and then dry it in a high-temperature oven at 105°C until the aggregate is saturated and dry, and then store it for later use; stir it every 10 minutes during the drying period;

[0067] S4: Add the mixture, natural coarse aggregate and 40% of water into the mixer and mix at a speed of 90 r / min for 60 s;

[0068] S5: adding cement, fly ash, silica powder and mineral powder into a mixer, stirring at a speed of 90 r / min, slowly adding a water reducer and 60% of water into the mixer during the stirring process, stirring evenly, and obtaining a concrete mixture;

[0069] S6: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0070] Example 7

[0071] S1: Weigh the following raw materials in parts by weight: 445 parts of Class III recycled fine aggregate (the aggregate water absorption rate is measured to be 10%), 5.28 parts of basalt fiber, 1245 parts of natural coarse aggregate, 392 parts of cement, 84 parts of fly ash, 56 parts of silica fume, 28 parts of mineral powder, 5.6 parts of water reducer, and 120 parts of water;

[0072] S2: Add recycled fine aggregate, basalt fiber and 10wt% potassium hydroxide solution into a mixer, stir evenly at a speed of 90r / min, let stand for 24h, and stir evenly every 6h; wherein the mass ratio of recycled fine aggregate to potassium hydroxide solution is 445:1000;

[0073] S3: Sieve the recycled fine aggregate and basalt fiber mixture with a sieve, rinse the mixture with clean water for 3 times, and then dry it in a high-temperature oven at 105°C until the aggregate is saturated and dry, and then store it for later use; stir it every 10 minutes during the drying period;

[0074] S4: Add the mixture, natural coarse aggregate and 40% of water into the mixer and mix at a speed of 90 r / min for 60 s;

[0075] S5: adding cement, fly ash, silica powder and mineral powder into a mixer, stirring at a speed of 90 r / min, slowly adding a water reducer and 60% of water into the mixer during the stirring process, stirring evenly, and obtaining a concrete mixture;

[0076] S6: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0077] Comparative Example 1

[0078] S1: Weigh the following raw materials in parts by weight: 445 parts of Class III recycled fine aggregate (the aggregate water absorption rate is measured to be 10%), 5.28 parts of basalt fiber, 1245 parts of natural coarse aggregate, 392 parts of cement, 84 parts of fly ash, 56 parts of silica fume, 28 parts of mineral powder, 5.6 parts of water reducer, and 120 parts of water;

[0079] S2: Add recycled fine aggregate, basalt fiber and deionized water into a mixer, stir evenly at a speed of 90r / min, let it stand for 24h, and stir evenly every 6h; the mass ratio of recycled fine aggregate to deionized water is 445:1000;

[0080] S3: The recycled fine aggregate and basalt fiber mixture is sieved out with a sieve, placed in a high-temperature oven at 105°C for drying until the aggregate is saturated and dry, and then stored for later use; during the drying period, the mixture is stirred once every 10 minutes;

[0081] S4: Add the mixture, natural coarse aggregate and 40% of water into the mixer and mix at a speed of 90 r / min for 60 s;

[0082] S5: adding cement, fly ash, silica powder and mineral powder into a mixer, stirring at a speed of 90 r / min, slowly adding a water reducer and 60% of water into the mixer during the stirring process, stirring evenly, and obtaining a concrete mixture;

[0083] S6: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0084] Comparative Example 2

[0085] S1: Weigh the following raw materials in parts by weight: 445 parts of Class III recycled fine aggregate (the aggregate water absorption rate is measured to be 10%), 5.28 parts of basalt fiber, 700 parts of pretreatment water, 300 parts of potassium hydroxide powder, 1245 parts of natural coarse aggregate, 392 parts of cement, 84 parts of fly ash, 56 parts of silica fume, 28 parts of mineral powder, 5.6 parts of water reducer, and 120 parts of water;

[0086] S2: Add recycled fine aggregate, basalt fiber and 30wt% potassium hydroxide solution into a mixer, stir evenly at a speed of 90r / min, let stand for 24h, and stir evenly every 6h; wherein the mass ratio of recycled fine aggregate to potassium hydroxide solution is 445:1000;

[0087] S3: Sieve the recycled fine aggregate and basalt fiber mixture with a sieve, rinse the mixture with clean water for 3 times, and then dry it in a high-temperature oven at 105°C until the aggregate is saturated and dry, and then store it for later use; stir it every 10 minutes during the drying period;

[0088] S4: Add the mixture, natural coarse aggregate and 40% of water into the mixer and mix at a speed of 90 r / min for 60 s;

[0089] S5: adding cement, fly ash, silica powder and mineral powder into a mixer, stirring at a speed of 90 r / min, slowly adding a water reducer and 60% of water into the mixer during the stirring process, stirring evenly, and obtaining a concrete mixture;

[0090] S6: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0091] Comparative Example 3

[0092] S1: Weigh the following raw materials in parts by weight: 445 parts of Class III recycled fine aggregate (the aggregate water absorption rate is measured to be 10%), 5.28 parts of basalt fiber, 850 parts of pretreatment water, 150 parts of potassium hydroxide powder, 1245 parts of natural coarse aggregate, 392 parts of cement, 84 parts of fly ash, 56 parts of silica fume, 28 parts of mineral powder, 5.6 parts of water reducer, and 120 parts of water;

[0093] S2: Add recycled fine aggregate, basalt fiber and 15wt% potassium hydroxide solution into a mixer, stir evenly at a speed of 90r / min, let stand for 24h, and stir evenly every 6h; wherein the mass ratio of recycled fine aggregate to potassium hydroxide solution is 445:1000;

[0094] S3: The recycled fine aggregate and basalt fiber mixture is sieved out with a sieve, placed in a high-temperature oven at 105°C for drying until the aggregate is saturated and dry, and then stored for later use; during the drying period, the mixture is stirred once every 10 minutes;

[0095] S4: Add the mixture, natural coarse aggregate and 40% of water into the mixer and mix at a speed of 90 r / min for 60 s;

[0096] S5: adding cement, fly ash, silica powder and mineral powder into a mixer, stirring at a speed of 90 r / min, slowly adding a water reducer and 60% of water into the mixer during the stirring process, stirring evenly, and obtaining a concrete mixture;

[0097] S6: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0098] Comparative Example 4

[0099] S1: Weigh the following raw materials in parts by weight: 445 parts of Class III recycled fine aggregate (the measured aggregate water absorption rate is 10%), 5.28 parts of basalt fiber, 850 parts of pretreatment water, 150 parts of potassium hydroxide powder, 1245 parts of natural coarse aggregate, 392 parts of cement, 84 parts of fly ash, 56 parts of silica fume, 28 parts of mineral powder, 5.6 parts of water reducer, 120 parts of water, and 44.5 parts of additional water (additional water = recycled aggregate mass * recycled aggregate water absorption rate);

[0100] S2: Add recycled fine aggregate, natural coarse aggregate, basalt fiber and 40% water into a mixer and stir at a speed of 90 r / min for 60 s;

[0101] S3: Add cement, fly ash, silica powder and mineral powder into a mixer and stir at a speed of 90 r / min. During the stirring process, slowly add a water reducing agent and 60% of water into the mixer and stir evenly to obtain a concrete mixture;

[0102] S4: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0103] Comparative Example 5

[0104] S1: Weigh the following raw materials in parts by weight: 445 parts of Class III recycled fine aggregate (the aggregate water absorption rate is measured to be 10%), 5.28 parts of basalt fiber, 850 parts of pretreatment water, 150 parts of potassium hydroxide powder, 1245 parts of natural coarse aggregate, 392 parts of cement, 84 parts of fly ash, 56 parts of silica fume, 28 parts of mineral powder, 5.6 parts of water reducer, and 120 parts of water;

[0105] S2: Add recycled fine aggregate, basalt fiber and 15wt% potassium hydroxide solution into a mixer, stir evenly at a speed of 90r / min, let stand for 48h, and stir evenly every 6h; wherein the mass ratio of recycled fine aggregate to potassium hydroxide solution is 445:1000;

[0106] S3: Sieve the recycled fine aggregate and basalt fiber mixture with a sieve, rinse the mixture with clean water for 3 times, and then dry the mixture in a high-temperature oven at 105°C until the aggregate is saturated and dry, and store it for later use; stir it every 10 minutes during the drying period;

[0107] S4: Add the mixture, natural coarse aggregate and 40% of water into the mixer and mix at a speed of 90 r / min for 60 s;

[0108] S5: adding cement, fly ash, silica powder and mineral powder into a mixer, stirring at a speed of 90 r / min, slowly adding a water reducer and 60% of water into the mixer during the stirring process, stirring evenly, and obtaining a concrete mixture;

[0109] S6: Load the mixture into a mold, vibrate and compact it, and cure it in a curing room at a temperature of 20°C and a humidity of 95% for 28 days.

[0110] Table 1 Content of each component in Examples and Comparative Examples

[0111]

[0112] Table 2 Recycled aggregate types and mechanical properties and chloride salt corrosion resistance of concrete

[0113]

[0114]

[0115] It can be seen from the test results of Examples 1-7 and Tables 1 and 2 that the C80 recycled fine aggregate concrete prepared by the present invention, after the mixed recycled fine aggregate and basalt fiber are soaked in a potassium hydroxide solution with a concentration of 10%-20% for 24 hours, the crushing value of the recycled fine aggregate is ≥25.1%, and the tensile strength of the basalt fiber is ≥3740. Among them, in Example 1-5, that is, the potassium hydroxide solution concentration is 15%, and the soaking pretreatment is 24 hours, which is the best pretreatment condition.

[0116] From the test results of Examples 1-7 and Tables 1 and 2, it can be seen that the C80 recycled fine aggregate concrete prepared by the present invention has a slump of ≥180 mm after curing for 28 days, and no segregation occurs. Its compressive strength is ≥80 MPa, and the chloride ion rapid diffusion coefficient is ≤2.8×10 -12 m 2 / s. Example 1 is the best mix ratio.

[0117] It can be seen from the data of Example 1, Comparative Example 4 and Tables 1 and 2 that, compared with the recycled aggregate concrete without pretreatment, the recycled fine aggregate concrete and basalt fiber are pretreated for a suitable time using a potassium hydroxide solution of an appropriate concentration, which can reduce the crushing value of the recycled fine aggregate by 14%, increase the tensile strength of the basalt fiber by 20%, increase the slump of the recycled aggregate concrete by 100%, increase the compressive strength by 81%, and reduce the rapid diffusion coefficient of chloride ions by 56%.

[0118] It can be seen from the data of Comparative Example 1, Example 1, Comparative Example 4 and Tables 1 and 2 that, compared with the recycled aggregate concrete without pretreatment, the recycled fine aggregate and basalt fiber mixed by water pretreatment can increase the slump of the recycled aggregate concrete by 89%, but has no strengthening effect on the aggregate and fiber, so the recycled aggregate concrete cannot reach the target strength and target durability.

[0119] From the data of Comparative Examples 2 and 5, Examples 1 and 6, and Tables 1 and 2, it can be seen that excessively high concentrations of potassium hydroxide solution and excessively long pretreatment times will damage the recycled fine aggregate and basalt fiber. The reasons may be: (1) the products of the alkali-silicon reaction that occur over a long period of time will damage the aggregate; (2) the highly alkaline potassium hydroxide will corrode the basalt fiber when in high concentration or for a long period of time. Therefore, it is impossible to make the recycled aggregate concrete reach the target strength and target durability.

[0120] It can be seen from the data of Comparative Example 3, Example 1 and Tables 1 and 2 that, since the excess potassium hydroxide solution was not rinsed off, the pH in the concrete was too high, resulting in a more violent alkali-silica reaction, the generated substances expanded, and the concrete produced internal cracks due to uneven stress, causing internal damage. Therefore, the recycled aggregate concrete could not reach the target strength and target durability.

[0121] It can be seen from the data of Comparative Example 4, Example 1 and Tables 1 and 2 that since the recycled fine aggregate and basalt fiber have not been pretreated, the prepared concrete has poor fluidity and is difficult to reach the target strength. The mechanical properties and resistance to chloride erosion are poor, so the recycled aggregate concrete cannot reach the target strength and target durability.

[0122] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing C80 recycled fine aggregate concrete, characterized in that: The steps include: S1: Weigh the following raw materials according to the following mass parts: 1205-1260 parts of natural coarse aggregate, 425-455 parts of recycled fine aggregate, 2.64-7.93 parts of basalt fiber, 540-580 parts of cementitious material, 5.4-5.8 parts of water reducer, and 111-124 parts of water; S2: Add recycled fine aggregate, basalt fiber and 10-20wt% potassium hydroxide solution into a mixer, stir evenly, let stand for 24 hours, and stir evenly every 6-8 hours; the mass ratio of recycled fine aggregate to potassium hydroxide solution is (425-455):1000; S3: The recycled fine aggregate and basalt fiber mixture is sieved out with a sieve, and after the mixture is rinsed with clean water, it is placed in a high-temperature oven at 105°C for drying until the aggregate state is saturated and surface dry, and then stored for later use; during the drying period, the mixture is turned over and stirred every 10 minutes; S4: Add the mixture, natural coarse aggregate and 40% water into a mixer and mix well; S5: Add the cementitious material into the mixer and mix well. During the mixing process, slowly add the water reducing agent and 60% of water into the mixer to obtain concrete.

2. The method for preparing C80 recycled fine aggregate concrete according to claim 1, characterized in that: The cementitious material includes cement, fly ash, silica powder and mineral powder in a mass ratio of 14:3:2:1; the mass ratio of water to cementitious material is 0.21; the mass ratio of natural coarse aggregate to recycled fine aggregate is 2.8; the mass ratio of the total mass of natural coarse aggregate and recycled fine aggregate to the mass ratio of cementitious material is 3.

3. The method for preparing C80 recycled fine aggregate concrete according to claim 1, characterized in that: The natural coarse aggregate is Class III or above crushed stone specified in GB / T14685-2022, with a particle size of 4.75-31.50 mm.

4. The method for preparing C80 recycled fine aggregate concrete according to claim 1, characterized in that: The recycled fine aggregate is Class III and above recycled fine aggregate specified in GB / T25176-2010, and has a particle size of 0.15-4.75 mm.

5. The method for preparing C80 recycled fine aggregate concrete according to claim 1, characterized in that: The water reducer is a polycarboxylic acid high-efficiency water reducer with a water reduction efficiency of 40%. The mass of the water reducer is 1% of the mass of the cementitious material.

Citation Information

Patent Citations

  • Recycled concrete doped with short-cut basalt fibers and recycled coarse aggregate

    CN107010896A

  • Method for preparing large-mixing-amount low-quality mineral admixture recycled cement-based product through microwave curing

    CN110510947A

  • Concrete rapid repairing material for road and preparation process thereof

    CN115521098A